Science and Technological Trends in Sports: The Present Scenario (International Journal of Food and Nutritional Sciences, 2022)
Wearable gadgets in sports measuring a few bodily or physiological amount of an characterhave already come to be part of every day existence for plenty humans. While such easy gadgetsoutput specially the statistical values of measured portions or matter activities, needs in game aregreater stringent